Circular Elastic Plates on Elastic Unilateral Edge Supports - Celep, Zekai; Turhan, Dog˘an; Al-Zaid, Rajeh Zaid (ASME International, 1988)
The response of an elastic circular plate supported unilaterally by elastic springs along its edge is studied. A load which is uniformly distributed along a circular arc of the plate is considered. The loss of the contact along the edge of the plate, the variations of deflections and those of reactions are presented. The influences of the position of loading, the spring constant, and Poisson’s ratio are shown in various figures.